Introdução ao evidencialismo em epistemologia - Danilevicz, Igor (2018)
This dissertation addresses the evidentialism in the light of contemporary analytical epistemology or the theory of knowledge, notably that sustained by Richard Feldman and Earl Conee. In the first part of the paper I approach the theories of internalist and externalist justification as theories that deal with the origin of justification. Then I try to relate them to theories about the structure of justification. From this perspective, internalism was related to foundationalism, coherentism and infinitism. And, externalism has been related to causal theory, tracking theory, reliabilism, and the theory of proper function. In the second part, the Evidentialist Theory of Judgment or Evidentialism in Conee & Feldman is discussed, where besides the definition of evidence I present the classification between synchronic justification and diachronic justification, as well as propositional justification and doxtic justification. The second part also examines the relationship between 'epistemic justification and truth' and the relation between 'evidence and belief', also addressing the principle of underdetermination and some objections to the evidentialism of Conee & Feldman.